Political dynasties - Ernesto Dal Bó; Pedro Dal Bó; Jason Snyder (Brown University, Department of Economics, 2006)
We study political dynasties in the United States Congress since its inception in 1789. We document patterns in the evolution and profile of political dynasties, study the self-perpetuation of political elites, and analyze the connection between political dynasties and political competition. We find that the percentage of dynastic legislators is decreasing over time and that dynastic legislators have been significantly more prevalent in the South, the Senate and the Democratic party. While regional and party differences have largely disappeared over time, the difference across chambers has not. We document differences and similarities in the profile and political careers of dynastic politicians relative to the rest of legislators. We also find that legislators that enjoy longer tenures are significantly more likely to have relatives entering Congress later. Using instrumental variables methods, we establish that this relationship is causal: a longer period in power increases the chance that a person may start (or continue) a political dynasty. Therefore, dynastic political power is self-perpetuating in that a positive exogenous shock to a person.s political power has persistent effects through posterior dynastic attainment. Finally, we find that increases in political competition are associated with fewer dynastic legislators, suggesting that dynastic politicians may be less valued by voters.
Keywords: D70; J45; N41; N42; 330; Political elites; dynasties; self-perpetuation; political selection; legislatures; Elite; Politiker; Macht; Geschichte; USA